Precision pharmacotherapy of atomoxetine in children with ADHD: how to ensure the right dose for the right person? - Guo, Hong-Li; Huang, Jian; Wang, Jie; Fan, Lin; Li, Yue; Wu, Dan-Dan; Liu, Qian-Qi; Chen, Feng (Frontiers in Pharmacology, 2024)
Non-stimulant atomoxetine is recognized in various current clinical guidelines as an important alternative to stimulants for the pharmacological treatment of attention deficit/hyperactivity disorder (ADHD) in children. While its efficacy and tolerability for core symptoms are established, there is considerable inter-individual variability in response and exposure, highlighting the need for personalized dosing. In this review, we evaluated existing studies and summarized comprehensive evidence supporting the clinical implementation of therapeutic drug monitoring (TDM) and personalized dosing of atomoxetine, organized around a series of logically structured questions. Although there are notable gaps in achieving personalized dosing across multiple critical elements, the available evidence is helpful to endorse personalized dose adjustments based on TDM and CYP2D6 genotyping "whenever possible". We advocate for ongoing improvement and enhancement in clinical practice. Future advancements will rely on a deeper understanding of ADHD, facilitating more precise diagnoses and personalized treatment strategies.